2021
DOI: 10.1080/00275514.2021.1952830
|View full text |Cite
|
Sign up to set email alerts
|

The core seed mycobiome ofPseudotsuga menziesiivar.menziesiiacross provenances of the Pacific Northwest, USA

Abstract: Fungal symbionts occur in all plant tissues, and many aid their host plants with critical functions, including nutrient acquisition, defense against pathogens, and tolerance of abiotic stress. "Core" taxa in the plant mycobiome, defined as fungi present across individuals, populations, or time, may be particularly crucial to plant survival during the challenging seedling stage. However, studies on core seed fungi are limited to individual sampling sites, raising the question of whether core taxa exist across l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…For bacteria, PCR amplification of the 16S rRNA genes was performed using the forward primer 27F (5′-AGAGTTTGA TCMTGGCTCAG-3′) and the reverse primer 1492R (5′-ACCTTGTTACGACTT-3′) [5,14]. Fungal ITS genes were performed using primers ITS1F (5′-CTTGGTCATTTAGA GGAAGTAA-3 ′ ) and LR3 (5 ′ -CCGTGTTTCAAGAC GGG-3 ′ ) [15][16][17]. The nearly full-length sequencing of 16S rRNA and ITS genes was carried out according to PacBio Sequel Systems powered by Single Molecule, Real-Time (SMRT) sequencing technology.…”
Section: The Nearly Full-length Sequencing and Bioinformatics Analysismentioning
confidence: 99%
“…For bacteria, PCR amplification of the 16S rRNA genes was performed using the forward primer 27F (5′-AGAGTTTGA TCMTGGCTCAG-3′) and the reverse primer 1492R (5′-ACCTTGTTACGACTT-3′) [5,14]. Fungal ITS genes were performed using primers ITS1F (5′-CTTGGTCATTTAGA GGAAGTAA-3 ′ ) and LR3 (5 ′ -CCGTGTTTCAAGAC GGG-3 ′ ) [15][16][17]. The nearly full-length sequencing of 16S rRNA and ITS genes was carried out according to PacBio Sequel Systems powered by Single Molecule, Real-Time (SMRT) sequencing technology.…”
Section: The Nearly Full-length Sequencing and Bioinformatics Analysismentioning
confidence: 99%
“…b matured seed disperse and becomes colonized from sources such as air (suggested in Gandolfi et al, 2013), water (Crocker et al, 2016), animals (Correia et al, 2019;Lash et al, 2020), soil (Fort et al, 2021), and other seeds in storage (suggested in Bergmann and Busby, 2021). Seed dormancy and germination are likely to represent a very active period of such horizontal transmission, as soil microbes interact with seed exudates and pre-existing microorganisms on and within the seed (Nelson, 1990;Ofek et al, 2011).…”
Section: Acquisition Modes Of Seed Microbiotamentioning
confidence: 99%
“…Several studies have shown that seed microbial communities differ significantly across geographic locations, i.e., at the macroscale, for example in B. napus (Morales Moreira et al, 2021), Elymus nutans (Guo et al, 2020), Phelipanche ramosa (Huet et al, 2020) and Pseudotsuga menziesii (Bergmann and Busby, 2021). For most of these studies, the abiotic factors that are important for structuring these seed microbial communities remain to be identified.…”
Section: Deterministic Processes: Abiotic Filtering Host Filtering An...mentioning
confidence: 99%
See 2 more Smart Citations